36-Context dynamic optically reconfigurable gate array - Nakajima, Mao; Watanabe, Minoru (2009 IEEE/SICE International Symposium on System Integration, 2009)
Optically reconfigurable gate arrays (ORGAs) have been developed for the purposes of realizing large virtual gates and increasing a gate array's performance by combining a holographic memory with a programmable gate array. In addition, dynamic optically reconfigurable gate arrays (DORGAs) using a photodiode memory architecture have been developed to realize a high-density VLSI. We have already demonstrated a 16-context DORGA architecture with a nanosecond-order reconfiguration capability. This paper presents a more advanced 36-context DORGA with performance that exceeds that of current dynamic reconfigurable devices.